Efektivitas Layanan Konseling Kelompok dalam Meningkatkan Empati Siswa - Lidia Putri, Elmi; Ardimen, Ardimen; Tas'adi, Rafsel; Gustina, Gustina (Jurnal Fokus Konseling, 2019)
The purpose of this study was to determine whether group counseling was effective in increasing student empathy. The type of research used was pre-experiment with type one group pretest-posttest design. The population in this study were all students of class X.1 of SMAN 1 Padang Ganting who were registered in the 2017/2018 school year, the sampling technique used to determine the sample was purposive sampling technique that is with certain considerations, consideration of researchers is students who are identified lacking empathy and not empathy with a sample size of 10 people. The results showed that group counseling had a significant effect on increasing student empathy. This is evidenced by the increase in the posttest score after being given treatment through group counseling. This means that t0 ttt so that Ha which states group counseling is effective in increasing student empathy is significantly accepted, and H0 which states that group counseling is not effective in increasing student empathy is rejected.